(2x-6)-1/3(9-4x)

Simple and best practice solution for (2x-6)-1/3(9-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-6)-1/3(9-4x) equation:


x in (-oo:+oo)

2*x-((1/3)*(9-(4*x)))-6 = 0

(-1/3)*(9-4*x)+2*x-6 = 0

2*x-1/3*(9-4*x)-6 = 0

2*x-1/3*(9-4*x)-6 = 0

10/3*x-6-3 = 0

10/3*x-9 = 0

10/3*x-9 = 0

10/3*x-9 = 0 // + 9

10/3*x = 9 // : 10/3

x = 9/10/3

x = 27/10

x = 27/10

See similar equations:

| 53=1-4p | | 3(3.2)+2y=32 | | -6-2r=-6 | | 4x-7=5-(2-x) | | 58=-5n-2 | | x+6+8=10-9 | | 63k^2+12k-96=0 | | 7j-7j+j+2j-j=10 | | 205=x+y | | P-15=20 | | F(x)=x-x+1 | | 110=-9-7k | | 5x+2(32-5x)=48 | | b^2-11b=10 | | -7x+10+8x=4+x+6 | | 10y+x=4(x+y) | | p^4-10p+9=0 | | X^4-3x^3+0x^2+x-3=0 | | 12×4/5 | | 4+7=3-4 | | 22=11.1 | | 3600=20x+15y | | F(x)=1-x | | 7×2/12= | | 6z+2z=7z-5 | | -79p+6p-2p+6+42= | | 4+2(x+8)=2(2x+2)+8 | | 71x-1x=-11x+132 | | H=4.9t-4.9t^2 | | 3x(7-2)+X(4-1)+8=2 | | 71-1x=-11x+132 | | 2q-q-q+2q=14 |

Equations solver categories